POLA KOMUNIIKASI ORANG TUA TUNGGAL DALAM MEMBENTUK KEDISIPLINAN PADA ANAK MENJALANKAN AJARAN AGAMA ISLAM DI KECAMTAN MEDAN HELVETIA - Dhoifatul Hasanah Selian (Sekolah Tinggi Ilmu Syariah (STIS) Al-Aziziyah Sabang, 2023)
This artickel is written with the aim to determine: 1). Single parent communication pattern in shaping the discipline implement the teachtings of Islam in the distrik of Medan Helvetia; 2). The impact of the lack of communication single parent to child discipline implement the teachings of Islam; 3). Constraints faced by single parent in child discipline implement the teachings of Islam; 4) Efforts are made single parent in child discipline implement the teachings of Islam. The method used in this research is qualitative method. After this research, it can be concluded as follows: 1). Pattern of communication single parent in shaping the discipline the of children carrying out the teachings of Islam in the district of Medan Helvetia is generally carried out at dinner, when relaxed or at the right times, in which the child is always with parent to prioritize the interests of children and control their children, being rational , always an underlying on the ratio or thoughts that are appropriate logic .; 2). The impact of the lack of communication singel parent to disciplin children implement the teachtings of Islam, among others changes in the behavior of children to be rigit (hard), tent to be emotional and to be refused, the child irritable, fearful, sad and feeling unhappy, easily distracted, stressed, have ni future direction clear front and unflidly, distracted chid psychologhy and identity crisis; 3). Contraints faced by singel parent in child discipline implement the teachings of Islam, among others, lack of time because of busy parent outside the home so as to give emphasis or affirmation to implement the teachings of Islam can not be done at any time. Insights parent who lack the understanding to discipline implement the teachings of Islam; 4). Efforts are made singel parent in child discipline implement the teachings of Islam among other approaches, put children into boarding school, implement house rules, punishment ang rewards. Keywords: Islamic Boarding School, Parents, Patterns and Communication